Analisis Ground Vibration pada Kegiatan Peledakan Overburden di Pit Timur PT Kuansing Inti Makmur, Jobsite Tanjung Belit, Kecamatan Jujuhan, Kabupaten Bungo, Provinsi Jambi - Intan Juita; Mulya Gusman (Departemen Teknik Pertambangan FT UNP, 2021)
PT Kuansing Inti Makmur is a national private company engaged in the coal miningindustry using the blasting method. Ground vibration is one of the negative impacts of blasting onthe environment and surrounding buildings if it exceeds the predetermined standard. This mininglocation is close to Tanjung Belit Village which is currently 500 meters from the settlementaccording to the direction of mining progress. The threshold value for ground vibration is 0.9mm/s based on the standards of PT Kuansing Inti Makmur. Ground vibration measurement datawere analyzed using scaled distance theory to obtain the effect of explosive charge and distance onPPV which was divided into two based on the row direction (Row B – T and Row S – U) in orderto get more referentative results. In the direction of row B – T using the power regression equation,based on the calculation results obtained by the equation PPV=4844,8 x-1,648. Meanwhile, for the direction of row S – U using the average calculation using Microsoft Excel, the equation PPV =3669,05 x-1.6 is obtained. The vibration safety method uses a longer delay in the middle of the segment. Based on the scaled distance theory, predictions of explosive charge are obtained toachieve the specified vibration standard, namely for row B – T 55,5 kg ANFO at a distance of1600 meters and row S – U 78,6 kg ANFO at a distance of 1600 meters. By using the blastingmethod with a longer delay in the middle of the segment, it is more effective to reduce vibrationaccumulation and predict vibrations with good material quality results.